Electrical and optical properties of newly synthesized glyoxime complexes - Aydogdu, Y; Yakuphanoğlu, Fahrettin; Aydogdu, A; Tas, E; Cukurovali, A (Editions Scientifiques Medicales Elsevier, 2002)
In this study, the electrical and optical properties of newly prepared Ni((LH2)-H-1) and Ni((LH2)-H-2) complexes have been investigated and the results obtained were analyzed. It is seen that these complexes have inorganic semiconductor properties. The activation energies (E-a) for the complexes were calculated by using Arrhenius plots and their optical band gaps have been determined through the optical spectra. Thermal probe measurements indicated that these samples have n-type of electrical conductivity. (C) 2002 editions scientifiques et medicales Elsevier SAS. All rights reserved.
Keywords: complex; inorganic semiconductor; activation energy